Recurrence of perianal Paget’s disease: Clinical case - Plazzotta, Cecilia; González, Daniel; Rodríguez, Gustavo; Londinsky, Mario; Homblas, Jacobo; Balboa, Oscar (Cirugía del Uruguay, 2004)
Perianal Paget's disease is a rare condition, characterized by belated diagnosis, a de/ay that may extend over severa/ years with consequent de/ay in treatment.